Asymmetric multiple information cryptosystem based on chaotic spiral phase mask and random spectrum decomposition. (1st January 2018) - Rafiq Abuturab, Muhammad
Highlights: A multiple image encryption using chaotic spiral mask and random spectrum decomposition is proposed. The multiple decryption keys in a single CSPM enhance the security levels. The different secret images are encrypted by different CSPMs using different parameters as decryption keys. CSPMs are easier to position in decoding process due to their own centering mark on axis focal ring. Simulation results are given to verify the feasibility and robustness of the proposed scheme. Abstract: A new asymmetric multiple information cryptosystem based on chaotic spiral phase mask (CSPM) and random spectrum decomposition is put forwarded. In the proposed system, each channel of secret color image is first modulated with a CSPM and then gyrator transformed. The gyrator spectrum is randomly divided into two complex-valued masks. The same procedure is applied to multiple secret images to get their corresponding first and second complex-valued masks. Finally, first and second masks of each channel are independently added to produce first and second complex ciphertexts, respectively. The main feature of the proposed method is the different secret images encrypted by different CSPMs using different parameters as the sensitive decryption/private keys which are completely unknown to unauthorized users. Consequently, the proposed system would be resistant to potential attacks. Moreover, the CSPMs are easier to position in the decoding process owing to their own centering mark on axis focal ring. The retrieved secret images are free from cross-talk noise effects. The decryption process can be implemented by optical experiment. Numerical simulation results demonstrate the viability and security of the proposed method.